2018
DOI: 10.1016/j.jcis.2018.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional nanomedicine with silica: Role of silica in nanoparticles for theranostic, imaging, and drug monitoring

Abstract: The idea of multifunctional nanomedicine that enters the human body to diagnose and treat disease without major surgery is a long-standing dream of nanomaterials scientists. Nanomaterials show incredible properties that are not found in bulk materials, but achieving multi-functionality on a single material remains challenging. Integrating several types of materials at the nano-scale is critical to the success of multifunctional nanomedicine device. Here, we describe the advantages of silica nanoparticles as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(77 citation statements)
references
References 182 publications
0
76
0
1
Order By: Relevance
“…SiNPs may naturally exist or be added to products by humans during fabrication or manufacturing. SiNPs have wide applications because of their unique properties and have been used in fields such as microelectronics [2], material science and industry [3], agriculture, food and consumer products (including cosmetics) [4][5][6][7], and medicine (drug delivery, diagnostic and medicine imaging and engineering) [8,9]. However, large-scale industrial SiNPs production and global SiNPs commercialization have increased human exposure risks [10].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…SiNPs may naturally exist or be added to products by humans during fabrication or manufacturing. SiNPs have wide applications because of their unique properties and have been used in fields such as microelectronics [2], material science and industry [3], agriculture, food and consumer products (including cosmetics) [4][5][6][7], and medicine (drug delivery, diagnostic and medicine imaging and engineering) [8,9]. However, large-scale industrial SiNPs production and global SiNPs commercialization have increased human exposure risks [10].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…It is an efficient way to impart water solubility to hydrophobic NPs and afford colloidal aqueous solutions, which are stable for extended periods of time. Furthermore it has already been used to efficiently develop imaging contrast agents [3,28] and recent studies have reported its degradation in biological media into non toxic silicic acid [29]. Reverse emulsion methods are particularly robust to prepare amorphous silica shells of tunable thickness and have been well developed to coat magnetite NPs [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, NPs composed of rare earth oxide have been reported as a new class of autophagy inducers [42,43]. Certain NPs, as those of silica, have been widely used in nanomedicine and other applications due to their biocompatibility [44,45]. However, when examined on the parameter of autophagy, these NPs came to cause impairment in lysosomal activity and cellular protein clearance [46,47].…”
Section: Discussionmentioning
confidence: 99%